Community level lipid profiling of consumers as a tool for soil food web diagnostics. Issue 5 (30th January 2018) - Kühn, Jakob; Richter, Andreas; Kahl, Tiemo; Bauhus, Jürgen; Schöning, Ingo; Ruess, Liliane
Abstract: Knowledge on food web structure and function provides important information on trophic relationships, energy flux, and ecosystem response to environmental changes. The tracing of trophic marker fatty acids (FAs) to assign predator–prey interactions is well established in food web research. However, the application on the level of entire consumer communities has not been performed yet. Here, we demonstrate that lipid pattern analysis of entire consumer assemblages can provide a first‐line assessment for food web diagnostics. The trophic diverse group of nematodes was used as a model and community level lipid profiling (CLLP) was performed. As prerequisite a lipid library was constructed, assigning FAs to their predominant organismic origin to disentangle phylogenetic (i.e. consumer lipid metabolism) from diet type effects on CLLP. The suitability of CLLP analysis was tested using 150 forest sites differing in management type and intensity across three German regions. The nematode CLLP reflected ecosystem conditions and thereby separated regions as well as forest habitats, that is, conifer and deciduous stands. CLLP further enabled to address if environmental properties acted on the level of consumers or their resource use or both. However, forest management intensity was poorly assigned, likely due to a predominant species‐specific impact, not represented on community basis. We propose CLLP as a fast and robust biochemical method for food web diagnostics in cryptic habitats such as soil or benthos. Provided that organismic assemblages compared are substantially different in lipid metabolism, CLLP give insight into changes in the composition of consumer communities as well as their major diet under field conditions.